2 - ‘Spaces of Resistance’– African workers at Shoprite in Maputo and Lusaka: DOI: 10.4314/ad.v31i1.22249 - Miller, Darlene (Africa Development, 2006)
South Africa’s reintegration into Southern Africa since 1994 has opened the way for renewed investments by South African firms in African countries. New shopping malls are one visible impact of this post-Apartheid development. This article is about the regional claims and the regional resistance of workers at the foreign branches of Shoprite, a South African retail multinational. Two shopping mall workplaces of Shoprite in Zambia (Manda Hill) and Mozambique (Centro Commercial) are the case studies for this analysis. The paper compares the experiences of retail workers at Shoprite, a South African food supermarket chain and Africa’s largest retailer, in two cities – Maputo, Mozambique and Lusaka, Zambia, exploring the variations and similarities in the responses of workers to their South African work environments. While Zambia’s ‘expectations of modernity’ have led to disillusionment, Mozambican workers accept South African investment as a necessary phase of Mozambique’s recovery. I argue that a new regional moment is shaping the workplace experiences of African workers, opening up a new ‘space of hope’ in the region. South African retail multinational corporations are important agents of a new regional imagination amongst retail workers in post-Apartheid Southern Africa.